The PI3K-Akt-eNOS pathway is involved in aortic hyporeactivity to Phenylephrine associated with late pregnancy in spontaneously hypertensive rats - Zancheta, Dalise [UNESP]; Troiano, Jessica A. [UNESP]; Potje, Simone R. [UNESP]; Cavalari, Priscila [UNESP]; Sumida, Doris H. [UNESP]; Antoniali, Cristina [UNESP] (Elsevier B.V., 2015)
Aim: This study aimed to evaluate the effects of Wortmannin, an inhibitor of phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt), on aortic hyporeactivity to Phenylephrine (Phe) and nitric oxide bioavailability associated with pregnancy in hypertensive rats.Main methods: The intact aortic rings of pregnant and non-pregnant Wistar or spontaneously hypertensive rats (SHRs) were stimulated with Phe (1 nmol/L to 10 mmol/L) before and after incubation with Wortmannin (10 nmol/L, 30 min). Western blot experiments analyzed the expression of phosphorylated PI3K [p85-PI3K], Akt [p-Akt (Ser 473)] and eNOS [p-eNOS (Ser 1177)] in aorta homogenates of pregnant and non-pregnant Wistar rats or SHRs. The effect of Wortmannin (10 nmol/L) on the cytosolic concentrations of nitric oxide (NO; measured using 4,5-diaminofluorescein diacetate [DAF-2DA], 10 mmol/L), Ca2+ (using Fluo 3-AM, 5 mu mol/L) and reactive oxygen species (ROS; using dihydroethidium [DHE], 2.5 mmol/L) were measured fluorimetrically in freshly isolated endothelial cells.Key findings: Wortmannin increases the reactivity of the aorta to Phe and decreases NO concentrations in the aortic endothelial cells of pregnant Wistar rats and SHR.Significance: The PI3/AKT/endothelial nitric oxide synthase (eNOS) pathway contributes to aortic hyporeactivity to Phenylephrine associated with pregnancy in normo- and hypertensive rats. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Wortmannin; Aorta; Phenylephrine; Pregnancy; Nitric oxide; Spontaneously hypertensive rats